Analysis of Theory of Planned Behavior (TPB) in Disobedience Behavior towards Occupational Health and Safety (K3) - Rhendy May Perdana (Journal of Economics, Business, and Government Challenges, 2021)
Work accident is one of problems which often occurs to workers at company. This accident usually happens because of the employee itself and working environment factors, especially entrepreneur factors. Occupational health and safety is one of protection aspects for labor which has arranged on the law of Republic Indonesia number 13 in 2003. Not a slight, the work accident is caused by Behavioral Disobedience against occupational health and safety. The aim of this research is to know and analyze Behavioral Disobedience against occupational health and safety by Analysis of Theory of Planned Behavior (TPB). Sample in this research is an employee who has region of work around Surabaya City, man/woman 17-55 years old. This research uses the technique of sampling about 104 respondents. The data analysis technique in this research uses Partial Least Square (PLS). The result of this research concludes that (1) attitude influences significantly positive effect to intention, (2) Subjective norm influences significantly positive effect to intention, (3) perceived behavioral control influences significantly positive effect to intention, (4) intention influences significantly positive effect to behavior, (5) perceived behavioral control influences significantly positive effect to behavior.